Dark compactons in nonlinear Schrödinger Lattices with strong nonlinearity management - Abdul Hadi, Muhammad Salihi; Umarov, Bakhram A.; Abdullaev, Fatkhulla Kh.; M, Salerno (Institute for Mathematical Research (INSPEM) Universiti Putra Malaysia, 2016)
The existence of dark compacton solution of discrete nonlinear Schrödinger (DNLS) equation with strong nonlinearity management (SNLM) is investigated. The stability analysis was carry out using standard linearization stability procedure.Even though the stability regime is not so wide but evidently some stable dark compactons can exist in the SNLM DNLS system. Surprisingly, even within the confirmed stability regime from the analysis, the time evolution of the dark compacton solution exhibits small bounded ripples.